Effects of RAAS blocker use on AKI in elderly hypertensive STEMI patients with propensity score weighed method. (4th July 2022) - Zeren, Gönül; Avcı, İlhan İlker and Sungur, Mustafa Azmi and Şimşek, Barış and Sungur, Aylin and Can, Fatma and Yılmaz, Mehmet Fatih and Gürkan, Ufuk and Kalkan, Sedat and Karagöz, Ali and Tanboğa, İbrahim Halil and Karabay, Can Yücel
ABSTRACT: Studies reported conflicting results on the effect of renin-angiotensin-aldosterone system (RAAS) blocker use on acute kidney injury (AKI) in patients undergoing elective coronary angiography but association in elderly patients with ST-elevation myocardial infarction (STEMI) is not known. Also, there are limited data on the effect of inflammatory markers on AKI. We aimed to investigate the effects of RAAS blocker pretreatment and inflammatory markers on AKI in this population. A total of 471 patients were compared according to presence of RAAS blocker pretreatment at admission. Conventional and inverse probability weighed conditional logistic regression were used to determine independent predictors of AKI. Mean age of the study group was 75.4 ± 7.1 years and 29.1% of the patients were female. AKI was observed in 17.2% of the study population. Weighted conditional multivariable logistic regression analysis revealed that AKI was associated with baseline creatinine levels and C-reactive protein/albumin ratio (CAR) (OR 2.08, 95% CI = 1.13–3.82, p = .02 and OR 1.19, 95% CI = 1.01–1.41, p = .04, respectively). No significant association was found between RAAS blocker pretreatment and AKI. CAR and elevated baseline creatinine levels were independent predictors of AKI in this patient group.